The Concept of Giving Punishment Perspective Ibnu Sahnun and Its Application to the Islamic Education System in Indonesia - Umam, Muhammad Rafli; Inayati, Nurul Latifatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This research is a qualitative research aimed at describing the concept of punishment by Ibnu Sahnun and its application in the Islamic education system in Indonesia. This research is motivated by Ibnu Sahnun's ideology, which states that the purpose of education is the formation of ethics in general, and this idea aligns with the prevailing regulations in Indonesia. Considering the low quality of moral education in Indonesia, the application of Ibnu Sahnun's concept of punishment can enhance the morality of students while still focusing on its educational significance. Ibnu Sahnun's method of punishment is closely tied to the Islamic education system as it is based on the Quran and Sunnah, aiming to nurture God-fearing individuals and develop dynamic human beings for both worldly and hereafter well-being. This approach also aligns with Indonesia's regulations on punishment, emphasizing that teachers should not use punishment solely for